Literature Review : The Role of Nutrition Management in Enhancing Economic Resilience of Disaster-Affected Communities - Hely, Hely; Damanik, Balqis Nurmauli (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2025)
Economic recovery after a crisis, such as a pandemic, is intricately linked to public health and nutritional well-being. Adequate nutrition is essential for maintaining productivity and labor capacity. This study investigates the relationship between daily nutritional intake (calories consumed) and economic recovery indicators, particularly income levels and productivity, in affected communities. A cross-sectional quantitative study was conducted involving 150 participants across five rural districts. Daily calorie intake was recorded using 24-hour dietary recall, and economic recovery was assessed via self-reported monthly income and weekly work hours. Regression analysis was employed to explore associations. Results showed a significant positive correlation (r = 0.62, p < 0.01) between daily caloric intake and monthly income. Participants with higher caloric intake (>2500 kcal/day) had 20–35% higher income levels and reported greater work productivity than those with lower intake. Adequate nutrition plays a key role in fostering economic resilience and productivity. Strengthening food access and dietary interventions can be effective strategies in supporting long-term economic recovery in vulnerable populations.